2020
DOI: 10.1016/j.amjcard.2020.06.053
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Value of Left Ventricular Global Longitudinal Strain in COVID-19

Abstract: ; societ a Italiana di cardiologia and the CCU academy investigators group. Reduction of hospitalizations for myocardial infarction in Italy in the COVID-19 era.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
29
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(38 citation statements)
references
References 4 publications
6
29
1
2
Order By: Relevance
“…Importantly, conventional assessment of LV function by LVEF did not reveal differences between groups of myocardial injury. In line with the findings of a recent study of Janus et al [ 7 ], we observed that rather LV-GLS than LVEF is the modality of choice to detect systolic left ventricular dysfunction (LVD sys ) in patients with COVID-19-associated myocardial injury. LVD sys was mainly detected by impaired LV-GLS (12 out of 19 patients with LVD sys ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Importantly, conventional assessment of LV function by LVEF did not reveal differences between groups of myocardial injury. In line with the findings of a recent study of Janus et al [ 7 ], we observed that rather LV-GLS than LVEF is the modality of choice to detect systolic left ventricular dysfunction (LVD sys ) in patients with COVID-19-associated myocardial injury. LVD sys was mainly detected by impaired LV-GLS (12 out of 19 patients with LVD sys ).…”
Section: Discussionsupporting
confidence: 91%
“…Previous echocardiographic reports of COVID-19 patients could not show impairment of left ventricular (LV) function by conventional ejection fraction (LVEF) [ 5 ]. Recent retrospective studies revealed that either left or right ventricular dysfunction was observed in longitudinal strain measurements, possibly predicting mortality in COVID-19 patients [ 6 , 7 ]. So far, advanced three-dimensional and strain echocardiography (3DSE) has been lacking as part of the comprehensive clinical evaluation of COVID-19 patients.…”
Section: Introductionmentioning
confidence: 99%
“…9 Abnormalities in RV strain and LV GLS have also been reported and indicate subclinical myocardial injury. 5 , 6 Importantly, CMR in a significant proportion of recovered COVID-19 patients revealed fibrosis and edema predominantly in the basal and mid LV segments, corresponding with our STE findings. 8 Case reports and series of patients with various forms of myocarditis, including influenza myocarditis, have described a similar pattern of reduced basal strain on STE.…”
Section: Discussionsupporting
confidence: 86%
“… 1 , 2 , 3 , 4 Various forms of myocardial injury, defined by elevated cardiac biomarkers and/or abnormalities on transthoracic echocardiography (TTE) and cardiac magnetic resonance imaging (CMR) have been reported. 2 , 5 , 6 , 7 , 8 , 9 TTE can be particularly useful in the inpatient setting to quickly and inexpensively evaluate regional myocardial injury, however due to the infectious risk to medical staff, routine echocardiography for all COVID-19 patients should be avoided. 10 …”
Section: Introductionmentioning
confidence: 99%
“…Ventricular strain has been shown to be a useful tool for prognostication in patients with acute respiratory distress syndrome (ARDS) [5]. Studies indicate the potential use of ventricular strain assessment for prognostication in patients with COVID-19 [6][7][8].…”
Section: Introductionmentioning
confidence: 99%